STRUKTUR KEPRIBADIAN TOKOH UTAMA DALAM NOVEL AKU WONG KAFIR KARYA TULUS SETIYADI - M. Wildan Ali Miharja Hariputra; Darni Darni (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research describes the personality structure of the main character, Sumirah, in the novel Aku Wong Kafir by Tulus Setiyadi. The method used is descriptive qualitative, and the approach taken is the literary psychology approach, using Sigmund Freud's personality structure theory, which includes the id, ego, and superego. The data source is the novel titled Aku Wong Kafir by Tulus Setiyadi. The research data consists of texts, words, sentences, narratives, and dialogues from the novel Aku Wong Kafir. This data was analyzed using data analysis methods comprising three parts: (1) data reduction, (2) data presentation, and (3) conclusion drawing. This research yields four main results. First, the character Sumirah experiences three structures: id, ego, and superego. The results of this study indicate that the personality structure of the main character Sumirah in the novel Aku Wong Kafir by Tulus Setiyadi is divided into three elements: id, ego, and superego.